Digital Competences in Higher Education Professors - Fernández Márquez, Esther (2018)
This article describes a university experience whose objectives were (a) to define the digital competences of professors, (b) to state how they use Information and Communications Technology (ITC), and (c) to know their perceptions on the importance of facilitating this type of competences in the students. Through the CODIPES questionnaire, a total of 53 professors from the Social and Legal Sciences area of the University of Malaga (2016/2017 academic year) were assessed. Among the conclusions obtained from this study, we underscore the importance given to ICTs in training and their consideration as such in the teaching and learning processes, pointing out several factors that have a bearing on their use, such as lack of time or resources, the individual's ideas, or lack of information.